School‐age children's neural sensitivity to horizontal orientation energy in faces. Issue 7 (23rd August 2017) - Balas, Benjamin; van Lamsweerde, Amanda E.; Saville, Alyson; Schmidt, Jamie
Abstract: Face processing mechanisms are tuned to specific low‐level features including mid‐range spatial frequencies and horizontal orientation energy. Behaviorally, adult observers are more effective at face recognition tasks when these information channels are available. Neural responses to face images also reflect these information biases: Face‐sensitive ERP components respond preferentially to face images that contain horizontal orientation energy. How does neural tuning of face representations to horizontal information develop? Behavioral results show that this information bias increases over time such that younger children have a reduced bias favoring horizontally‐filtered faces that increases with age. In the present study, we chose to investigate how neural sensitivity to these low‐level features develops in the same age range, using ERP as a means of studying children and adults. Specifically, we examined how both face‐sensitive ERP components (the P100 and N170) changed their responses to faces and non‐faces as a function of age and orientation energy. Briefly, we found that the latency of the P100 and N170 component across age groups was consistent with the gradual emergence of a bias favoring horizontal orientation energy during middle childhood. The amplitude of the N170 component, however, exhibited a more complicated developmental profile that does not easily map onto previous behavioral results obtained from children in the same age ranges.